Pembentukan Kelompok Asuhan Mandiri Tanaman Obat Keluarga (TOGA) dan Akupresur di Kecamatan Sanden, Kabupaten Bantul - Suryani Hutomo; Yanti Ivana Suryanto; Novika Kurniawati (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
In Sanden, Bantul, there were several family started managing the yard by planting medicinal plants for sale, but there was still a lot of yard was not optimally utilized. The purpose of establishing independent medicinal plants (TOGA) and acupressure groups is to increase the active participation of the community in improving their health by changing the curative paradigm to be promotive and preventive, also to improve the family economy through planting and processing TOGA grown in the yard. The activity was carried out by establishing an independent TOGA and acupressure groups in several areas managed by their own groups. In line with this activity, the Bantul Government routinely organized greenery and medicinal plants competition for each village. The goal of the competition is, besides the environment being green, the medicinal plants can help the family's economic needs.